Increasing the Dietary Concentration of Lupinus albus L. Decreased Feed Intake and Daily Gain of Immunocastrated Male Pigs - Karen L. Moore; Emalyn Loudon; Frank R. Dunshea (Animals, 2021)
An experiment was conducted to determine the appropriate dietary concentration of albus lupins that would lower feed intake and decrease backfat while optimizing the effect on the growth rate of immunocastrated male pigs. The pigs were fed albus lupins (varying from 0 to 200 g/kg) from 2 weeks after the last immunization against GnRF for 14 d prior to slaughter (where d 0 is the day of the last immunization against GnRF). Increasing the dietary albus lupin concentration decreased daily gain for d 15 to 28 (p = 0.004). Daily feed intake also decreased as the concentration of the albus lupins increased for d 15 to 28 (p < 0.001). Carcass weight and backfat decreased as the concentration of dietary albus lupins increased (p = 0.011 and p = 0.024, respectively). The albus lupin concentration to maximize growth rate, minimize feed intake, maximize carcass weight and minimize backfat depth was 120, 142, 62.7 and 138 g/kg, respectively.